Strategi Peningkatan Mutu Pendidikan Tahfizh di SD PTQ Annida Salatiga - Ahmad Fikri Sabiq (Journal of Islamic Education Management, 2021)
This study aims to find out the strategies implemented by the principal in order to improve the quality of tahfizh education in SD PTQ Annida Salatiga. This study is a field study with a qualitative approach. The location of this study is in SD PTQ Annida Salatiga, Central Java. Data collection techniques are through interviews, observations, and documentation. Data analysis techniques in this study include the stages of data condensation, data presentation, and drawing conclusions. There are 3 aspects that are targeted from improving the quality of tahfizh education. First, the improvement of the quality of human resources in this case is reserved for teachers who support the tahfizh program. This improvement in the quality of human resources is implemented through teacher self-training, learning supervision, lesson study and peer assessment, as well as the construction of recitations. Second, the implementation of standard operating procedures (POS) implemented by tahfizh teachers in teaching. Third, improve communication and good cooperation with parents.